Forcing of western tropical South Atlantic sea surface temperature across three glacial-interglacial cycles - Hou, Alicia; Bahr, André; Schmidt, Stefan; Strebl, Cornelia; Albuquerque, Ana Luiza; Chiessi, Cristiano M.; Friedrich, Oliver (Global and planetary change, 2020)
The western tropical Atlantic (WTA) supplies warm and saline waters to the upper-limb of the Atlantic Meridional Overturning Circulation (AMOC) and may store excess heat and salinity during periods of AMOC slowdown. Since previous sea surface temperature (SST) reconstructions from the WTA typically focus on the Last Glacial Maximum and the last deglaciation, additional long-term records spanning multiple glacial-interglacial transitions are needed in order to elucidate the drivers of long-term WTA SST variability. We performed Mg/Ca analyses on the surface-dwelling planktic foraminifera Globigerinoides ruber (pink) from a sediment core raised from the southern WTA to reconstruct SST changes over the past 322 kyr. We evaluate the relative importance of atmospheric pCO2, AMOC strength and trade-wind intensity in driving the thermal evolution of the WTA across three glacial-interglacial cycles. Our results indicate a lack of pronounced glacial-interglacial variability in the SST record, prompting us to exclude atmospheric pCO2 as a direct driver of SST variations in the southern WTA. Similarly, we conclude that variations in AMOC strength also likely did not have a strong influence on long-term WTA SST, based on the low and relatively stable interhemispheric SST gradient over the past 322 kyr. Our results reveal high-amplitude variability in zonal SST gradients within the (sub)tropical South Atlantic and similarities between the long-term patterns of the intrahemispheric meridional SST gradient and our SST record. Based on these findings, we propose that changes in the intrahemispheric meridional SST gradient modulate southeast trade wind intensity, which in turn drives variations in zonal SST gradients and southern WTA SSTs.
Gesehen am 12.05.2020